Experiential Marketing Strategy in increasing MSME OnlineShop Customer Loyalty : Overley Visualization Bibliometric Analysis - Iva Khoiril Mala; Sudarmiatin (Formosa Journal of Applied Sciences, 2023)
The purpose of this research Explaining progress in the field of online shop by MSME actors is now a necessity that plays an important role in all circles of society. In the mindset of an increasingly modern society due to the many globalization competitions shown by the world, the creation of marketing strategies is rapid. This type of research uses bibliometrics using the VosViewer application. Application of experiential marketing through angles online shop conducted by MSMEs is very good and can be felt by consumer. The value of influence satisfaction on consumer loyalty is considered low which can also be due to the fact that new consumers are low loyal to one sales product in the UMKM online business means only old consumers who remain loyal to the product or service process offered. As a basic online shop MSME actor, it is mandatory to classify which ones are consumers who are already at the loyal level or are still in a satisfied state .